Transport Policies for the Euro-Mediterranean Free-Trade Area : An Agenda for Multimodal Transport Reform in the Southern Mediterranean - Muller-Jentsch, Daniel (Washington, DC: World Bank, 2013)
This study argues that the 15 European Union (EU) countries and their 12 Mediterranean Partners should complement their Euro-Mediterranean free-trade area for industrial goods with a common transport space. This would require the removal of policy-induced frictions in the region's multi-modal transport system in order to facilitate the flow of foods, people, and investments within this emerging trade block. The purpose of this report is to identify the bottlenecks and inefficiencies that currently exist and to map out the reforms in the legal, regulatory, and institutional framework that should be implemented to address them. This includes both national and cross-border policy measures in the various modes (air, maritime, and land-based transport) as well as in transport logistics. The study compares sector performance and sector policies within the concerned countries and it benchmarks these against international best practice. It draws on policy lessons from other developing regions, such as Latin America and Eastern Europe and assesses the extent to which the policy framework of the EU Single Market in the transport sector could provide guidance for the creation of a common transport space throughout the Mediterranean region.